The First Women’s ordination in the Episcopal Church of the 1970s - Posternak Andrei, priest (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Episcopal Church of the USA in 1976 adopted a positive resolution (1976-B300) regarding women’s ordination to the priesthood and episcopacy. The Church thus legalizes the experience of the Anglican community of the East coast: Philadelphia and Washington where in July 1974 and September 1975, took place women’s ordination. The article is devoted to the history of these ordinations, public reactions to them and theological discussions concerning the permissibility of female ordination in the Episcopal community of the ﬁrst half of the 1970s. The research is based on the oﬃ cial reports of the Episcopal Church. Believe in the Divine will on the vocation of women to the priesthood was associated with transformation of the Western society: women’s struggle for their rights and public struggle against race discrimination. The Anglican bishops were concerned about the problem of adaptation of the new ministry to modern conditions: the 1970s became a period of transition from traditional to post-Christian society in which gender was considered as a new social function. It will transform the Anglican community where the priesthood will become a form of ministry to the parish and in these conditions women can be ordained .